Pergeseran Makna Kata Antum Dalam Interaksi Sosial Santri Pondok Pesantren Miftahul Qulub Polagan Galis Pamekasan - Ainur Rizqi, Alfi; Veri Setiawan, Ahmad; Varah Adibah El fu'adi, Alvi; Murteza, Muhammad Ali; Fakhriyah, Sani (STIQ Amuntai, 2024)
Dhamir or in Indonesian is known as pronouns. In Arabic, dhamir itself is an isim ma'rifah which is used to represent the mention of something, someone, or a group. This study aims to describe two main aspects, namely how santri use the word antum in daily interactions, and the relationship between the use of the word antum and the attitude of language politeness. This research is descriptive research with a qualitative approach. The research data were obtained through participant observation and unstructured interview methods, the population of the object of this research is all active students in the Miftahul Qulub Polagan Galis Pamekasan Islamic boarding school, and 30 samples were taken. The informants of this research were 25 active students from the Miftahul Qulub Polagan Galis Pamekasan Islamic boarding school and there were 5 informants who had the status of being active teachers and administrators at the Miftahul Qulub Polagan Galis Pamekasan Islamic boarding school. Data processing was carried out by researchers using triangulation in the form of triangulation of methods, and triangulation of data sources. The results showed that First, this word is used as a pronoun to refer to the second male person in the plural. In the context of nahwu which is the grammatical rule of Arabic. Second, the word antum is used as a word of greeting to older individuals and individuals who are respected and respected. Third, the use of the word antum by santri is not only a functional communication tool, but also reflects the values of politeness in their culture. this research provides an in-depth understanding of how the word antum not only functions as a communication tool, but also as an expression of politeness values in the daily interactions of the santri.